DETERMINANTS OF GREEN PRODUCT PURCHASE BEHAVIOUR AMONG YOUNG ADULTS IN MALAYSIA: A CONCEPTUAL PAPER - Azli, Nur Syafiqah; Yasin, Nurul Hafizah Mohd; Samsudin, Norsuriani (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Green product purchasing among young adults in Malaysia has become increasingly important in supporting sustainable consumption practices. Despite increasing interest in green consumption, limited studies integrate marketing-related factors with psychological determinants within the Malaysian youth context. This conceptual paper aims to identify the key determinants influencing green product purchase behaviour among young adults in Malaysia. Specifically, the study focuses on the effects of eco-labels, attitude, environmental consciousness, green advertising, and green perceived quality on green product purchase behaviour. Grounded in the Theory of Planned Behaviour (TPB), the proposed framework explains how these factors shape young adults’ purchasing decisions toward green products. This paper synthesises existing literature and develops a conceptual model to guide future empirical research. It is anticipated that findings from subsequent empirical studies will provide valuable insights for marketers and policymakers in designing effective strategies to promote sustainable consumption among young adults in Malaysia.